Employment, Social Support, and HIV Sexual-Risk Behavior in Puerto Rican Women - Dixon, Denise A. (2001)
This study examined psychosocial factors associated with HIV-risk behavior among Latina women at self-disclosed heterosexual risk for HIV infection. Data were collected via structured interviews for 187 Puerto Rican women, aged 18–35, who attended a health clinic in the Bronx, New York. Over 64% of all participants reported unprotected vaginal sex with primary sexual partners. Higher levels of unprotected vaginal sex were associated with living with the partner, residing with children, current employment, heightened negative mood, and greater social support from the partner. The relationship between increased negative mood and increased unprotected vaginal sex use was mediated by employment, after controlling for educational level, living with the partner, and residing with children. The findings suggest that interventions designed to facilitate HIV-protective behaviors may need to consider that employment may supercede relationship factors among populations of urban women identified at increased heterosexual risk for HIV infection.